تحليل مهارة المحادثة باللغة العربية لدى طلا ب الصف الثاني عشر في مدرسة الثا نوية الحكومية 1 آتشيه الجنوبية الشرقية - Hidayah Syahfitra; Akmal Walad Ahkas (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
This study aims to analyse the muhadatsah (Arabic conversation) skills of 12th grade students in MAN 1 Southeast Aceh. The problems identified include students' limited ability to practice Arabic conversation because many students do not recognise the Arabic script, resulting in a lack of basic knowledge to learn Arabic. In addition, there is low student interest in learning Arabic, limited resources and facilities for learning Arabic, and monotonous teaching methods. The research uses a qualitative descriptive method. Data collection techniques include observation, interviews and documentation. The informants for this study are the 12th grade students, the Arabic language teacher, and the principal of MAN 1 Southeast Aceh. The results show that the 12th grade students at MAN 1 Southeast Aceh have little interest in learning Arabic, which affects their ability to practice Muhadatsah. However, the Arabic teacher has made efforts to increase the students' interest and skills in learning Arabic.